Spatio-temporal variation in synthesis of some nutraceutical components of thorowax foldwing (Dicliptera bupleuroides Nees) - Ahmad, Iftikhar; Ahmad, Muhammad Sajid Aqeel; Hameed, Mansoor; Muneeb, Ahmed; Imran, Muhammad; Hussain, Mumtaz; Ahmad, Farooq; Ahmad, Farooq; Asghar, Ansa; Basharat, Sana; Fatima, Sana; Parvez, Iqra; et al. (International Journal of Applied and Experimental Biology, 2024)
The present research was carried out to determine the spatiotemporal variation in accumulation of different nutritional and medicinal components in Dicliptera bupleuroides from the Soone valley in the Salt Range of Punjab, Pakistan. Most of the biochemical attributes were higher in the spring season than those in the other seasons; this might have been due to high soil pH during spring. High amounts of minerals and high pH are necessary for the synthesis of alkaloids, phenols, flavonoids, and fibers. Proteins, N, dry matter, fats and nitrogen free extract (NFE) were higher in summer, which might have been due to considerable availability of macro-nutrients during this season due to high moisture content because of high rainfall during the season. Spatial variation showed that phenols and flavonoids were associated with the population from Khabeki site (despite enough minerals and moisture availability) which might have been due to physical injuries caused by grazing and cutting. Minerals, proteins and N were also associated with the Khabeki population probably due to large amounts of minerals and moisture retention in the soil of the site and prevalent optimum environmental conditions therein. Alkaloids, fats, moisture and some minerals were associated with Anga and Knotti Garden sites which might have been due to high pH and prolonged salt stressed conditions at both sites.